Development of Ecotourism Mangrove Rambai Center in Anjir Muara District, Barito Kuala Regency, South Kalimantan Province Based on Local Potential - Susanto August Satria; M. Romi Bahtiar; Titon Srihardian; Ihsan Sanjaya Akbar; Fikri Jati Wibowo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
PT Pertamina Integrated Terminal Banjarmasin is one of the work units of PT Pertamina Patra Niaga which is a state-owned enterprise (BUMN) engaged in managing oil and gas (MIGAS). Like corporations, Pertamina IT Banjarmasin also has a Corporate Program Social Responsibility (CSR) as a form of responsibility and commitment in realizing a business based on sustainability, one of the CSR programs is the Rambai Center Mangrove Ecotourism Program. Method used in implementation until the preparation of scientific papers as outputs is carried out in several stages including elements of planning, implementation, until the results achieved. The results of the activities are shows of Pertamina's participation in increasing community participation through empowerment programs in maximizing local resources that have an impact on increasing economic levels and welfare through the development of MSMEs, contributing to conservation of mangrove ecosystems and proboscis monkeys, to contributing to education by maximizing ecotourism programs as places and facilities. learning and research.